Cardiac Function in Patients with Early Cirrhosis during Maximal Beta-Adrenergic Drive: A Dobutamine Stress Study - Krag, Aleksander (Public Library of Science, 2014)
BACKGROUND AND AIM: Cardiac dysfunction in patients with early cirrhosis is debated. We investigated potential cardiac dysfunction by assessing left ventricular systolic performance during a dobutamine stress test in patients with early cirrhosis. PATIENTS AND METHODS: Nineteen patients with Child A and B cirrhosis (9 with non-alcoholic cirrhosis) and 7 matched controls were included. We used cardiac magnetic resonance imaging to assess left ventricular volumes and cardiac output (CO) at rest and during maximal heart rate induced by increasing dosages of dobutamine and atropine. RESULTS: Patients with cirrhosis and controls had an equal stress response, the heart rate and ejection fraction increased similarly and maximal heart rate was reached in all. At rest CO was higher in Child B patients than controls. During maximal stress, Child B patients had higher CO (10.6±2.7 vs. 8.0±1.8 L/min), left ventricle end diastolic volume (90±25 vs. 67±16 mL), left ventricular end diastolic volume (10±4 vs. 6±2 mL) and stroke volume (80±23 vs. 61±15 mL) than Child A patients. The systemic vascular resistance was lower in Child B than Child A patients (670±279 vs. 911±274 dyne*s*cm(−5)). The left ventricle mass increased by 5.6 gram per model for end stage liver disease (MELD) point. MELD score correlated with the end diastolic and systolic volume, CO, and stroke volume at rest and at stress (all p<0.05). CONCLUSION: In patients with early cirrhosis the chronotropoic and inotropic response to pharmacological stress induced by dobutamine is normal. With progression of the disease, the mass of the heart increases along with increase in cardiac volumes.